Jefferson's Declaration of Independence : Origins, Philosophy, and Theology - Jayne, Allen (Book collections on Project MUSE., 2015)
Allen Jayne analyzes the ideology of the Declaration of Independence -- and its implications -- by going back to the sources of Jefferson's ideas: Bolingbroke, Kames, Reid, and Locke. He concludes that the Declaration must be read as an attack on two claims of absolute authority: that of government over its subjects and of religion over the minds of men. Today's world is more secular than Jefferson's, and the importance of philosophical theology in eighteenth-century critical thought must be recognized in order to understand fully and completely the Declaration's implications. Jayne addresses.